The impact of mine tailings on snouted harvester termites, Trinervitermes trinervoides (Sjostedt) (Isoptera: Termitidae), in the Vaal river region - Field, Megan Ann (My University, 2012)
Mining activities are well known for their negative effects on the environment and animals, due to the deposition of large volume of wastes in the form of tailings on the soil. These wastes or tailings contain high levels of heavy metals, sulphides and cyanide. Heavy metals are one of the most persistent pollutants in the environment and have been shown to bioaccumulate in animals. The purpose of this investigation was to evaluate the impact of mine tailings on the snouted harvester termite, Trinervitermes trinervoides, inhabiting the Vaal River region. These termites play a significant role in the food chain as they provide a proteinand energy-rich food source to numerous predators therefore any bioaccumulation of heavy metals may adversely impact the food chain. Three aspects of the termite biology was studied, namely, the density and distribution of the termite mounds, the temperature profile of the mounds and the heavy metal content of the termites, mounds and surrounding soil. Three sites were chosen in accordance to their position relative to a tailings dam with the furthest site being the Control site. The most contaminated site and site closest to the tailings dam (AEL site) had the highest termite mound density, followed by the least contaminated site (Control site) and then the intermediately contaminated site (West Complex). The AEL site had many incipient mounds but few large mounds indicating that although there was a high turnover of new mounds, the longevity of these mounds was low. Higher densities at the AEL site may be explained by the water table being closer to the surface as a result of the tailings dam, allowing the termites easier access to water and hence a more favourable environment within the mound. The centre temperatures of the mounds at all three sites were kept constant on a monthly basis but fluctuated on a seasonal basis. The West Complex site had the highest and most variable centre mound temperatures. The average heavy metal content of the surface layer did not differ significantly from the average heavy metal content of the mounds at the AEL and West Complex site, indicating that the termites are not making heavy metals more bioavailable to the environment. The termites at the AEL site had the highest levels of Cu and Zn out of all the sites and accumulated these metals to levels toxic to mammals. Alates (a major food source for many animals) however, did not accumulate any heavy metals therefore it is unlikely the food chain is being negatively impacted by the termites. From this study there is no indication that the snouted harvester termite density or behaviour are being impacted by the tailings dams